EFFECTIVENESS OF CAUCUSES IN PEACE AGREEMENTS BY MEDIATION IN RELIGIOUS COURTS A STUDY IN THE TEBING TINGGI RELIGIOUS COURT - Ahmad Junaidi; Azhali Siregar; Henry Aspan (PT. Sinergi Legal Publisher, 2025)
Mediation is a dispute resolution mechanism that is required before a case is examined in court, as regulated in Supreme Court Regulation (PERMA) Number 1 of 2016. One method in mediation that aims to increase the effectiveness of dispute resolution is caucus, which is a separate meeting between the mediator and one party without the presence of the other party. This study analyzes the effectiveness of the caucus method in achieving peace in divorce cases at the Tebing Tinggi Religious Court. The approach used is sociological juridical with a qualitative descriptive method through document studies and observations of the divorce mediation process. The results of the study indicate that the caucus method has a strategic role in helping the parties reveal hidden interests, calm emotions, and build trust in the mediation process. However, the effectiveness of this method is still influenced by various factors, such as minimal understanding of the parties regarding the function of the caucus, the limited time for mediation which is only 30 days, and the mediator's skills in utilizing this session optimally. Other obstacles faced include distrust between the parties, resistance to mediation, and lack of legal understanding regarding the caucus in PERMA No. 1 of 2016. To overcome these obstacles, it is necessary to increase public understanding of the benefits of mediation, as well as strengthening more detailed regulations regarding the procedures for implementing caucuses in PERMA. In addition, mediators must improve their skills in building trust and digging for information effectively in caucus sessions. By optimizing the caucus method, it is hoped that mediation can become a more efficient alternative for resolving disputes, reducing the burden of cases in court, and providing a more humane solution in divorce cases.